2013
DOI: 10.4028/www.scientific.net/amr.686.65
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of the Effect of Polymer Solution and Suspension Properties on the Electrospinning of Nanocomposite Fibers

Abstract: Nanocomposite fibers produced via electrospinning have very large surface area by virtue of their nanometer diameter sizes thereby making them very attractive for various applications such as for adsorption of contaminants from wastewater. In this study, a highly adsorbing nanoparticle, iron-modified montmorillonite was used as filler in the nanocomposite. The effects of polymer solution and suspension properties such as polymer concentration, clay loading, and filler type on the electrospinning of the nanocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The advantages of ACNF are smaller fiber diameter (which minimizes diffusion limitations and allows rapid adsorption and desorption), more concentrated pore size distribution, and excellent adsorption capacity at low concentrations, in comparison with conventional activated granular or powdered carbons [6]. Typically, an ACNF is a microporous carbonaceous adsorbent exhibiting slit-shaped pores.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of ACNF are smaller fiber diameter (which minimizes diffusion limitations and allows rapid adsorption and desorption), more concentrated pore size distribution, and excellent adsorption capacity at low concentrations, in comparison with conventional activated granular or powdered carbons [6]. Typically, an ACNF is a microporous carbonaceous adsorbent exhibiting slit-shaped pores.…”
Section: Introductionmentioning
confidence: 99%
“…To provide ease of handling and easier separation from wastewater, the immobilization of the clay particle in a polycaprolactone (PCL) nanofiber matrix through electrospinning was previously studied. Araño et al (2013) researched on the effect of solution properties such as viscosity and polymer-solvent-clay ratio on fiber diameter and bead formation [6]. Somera et al (2019) and Dela Peña et al (2012) showed the effectivity of the Fe-MMT/PCL nanofiber mat in adsorbing Hg (II) and As (V) ions, respectively [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Araño et al (2013) researched on the effect of solution properties such as viscosity and polymer-solvent-clay ratio on fiber diameter and bead formation [6]. Somera et al (2019) and Dela Peña et al (2012) showed the effectivity of the Fe-MMT/PCL nanofiber mat in adsorbing Hg (II) and As (V) ions, respectively [2,7]. There has been no studies on the effect of processing parameters such as voltage, suspension flow rate, tip-to-collector distance (TCD), and needle diameter on the particular polymer-solvent-filler system.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters involved in the development of TE scaffolds using electrospinning process can be divided into two main categories: materials aspect and machine parameters. In terms of materials, many researchers have studied solution parameters such as concentration of solution, 4161 concentration of fillers or additives, 41,46,48,55,62 solvent ratio, 43,48,52,57,63 conductivity, 42,53 and volatility of solution. 42 The second category, process parameters, was also analyzed by many researchers in terms of applied voltage, 4244,46,47,4960,62,64 needle diameter, 43,46,62 flow rate, 43,44,46,47,50,51,53,…”
Section: Introductionmentioning
confidence: 99%
“…42 The second category, process parameters, was also analyzed by many researchers in terms of applied voltage, 4244,46,47,4960,62,64 needle diameter, 43,46,62 flow rate, 43,44,46,47,50,51,53,55,56,62,64 rotational speed, 46,64 tip to collector distance 42,44,4652,54,56,62,64 , and spinning time. 43 The mentioned parameters were varied to investigate the effect toward several responses such as fiber diameter, 41,43,4655,5760,…”
Section: Introductionmentioning
confidence: 99%